ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK UMUM SYARIAH DENGAN METODE ISLAMICITY PERFORMANCE INDEX DAN MARKET VALUE ADDED - Noval, Sahrul; Isfandayani, Isfandayani (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2023)
This study aims to analyze the comparison of the financial performance of Islamic Commercial Banks using the Islamicity Performance Index (IPI) and Market Value Added (MVA) methods. The study period covers the years 2018-2021. This research employs a quantitative method with a descriptive approach. The study population includes all Islamic Commercial Banks registered with the Financial Services Authority (OJK) during 2018-2021. The sampling technique used is purposive sampling, resulting in three Islamic Commercial Banks listed on the Indonesia Stock Exchange. The data analysis method involves descriptive analysis and using the Cartesian Diagram of IPI and MVA to determine the position of the Islamic Commercial Banks. The results of this study show that there are four quadrants in the Cartesian diagram, but only two quadrants are occupied by Islamic Commercial Banks. Firstly, Quadrant I, or the Upper Left Quadrant (ULQ), is occupied by Bank Tabungan Pensiunan Negara Syariah (BTPNS) and Bank Syariah Indonesia (BSI), indicating that these two banks have high Market Value Added (MVA) but low Islamicity Performance Index (IPI). Secondly, Quadrant IV, or the Lower Right Quadrant (LRQ), is occupied by Bank Panin Dubai Syariah, indicating that this bank has a high Islamicity Performance Index (IPI) but a low Market Value Added (MVA). Meanwhile, no banks occupy Quadrant II or the Lower Left Quadrant (LLQ) and Quadrant III or the Upper Right Quadrant (URQ), indicating that no banks have both low IPI and MVA or both high IPI and MVA.